Improved Setpoint Adjustment for Ultrasonic Motors. - Schulte, Thomas; Fröhleke, Norbert
Speed control strategies for piezoelectric driveshave been presented by several authors. Beside various con-trol strategies based on adaptive structures like MIAS,MRAS, neural nets or Fuzzy control, a completely modelbased control system using an inner bending wave controland an outer speed control including a torque calculator for linearization has been presented. This paper deals with investigations and improvements of this torque calculator. The setpoint adjustment is focused toutilize the degrees of freedom for the bending wave values, which represents an additional potential for optimization of the performance of the drive system. Theoretical and experi-mental results confirm the advances.